TINGKAT MOTIVASI DAN PERILAKU KALANGAN MASYARAKAT DALAM BERBELANJA ONLINE MELALUI APLIKASI SHOPEE - Laidya Amalia Putri; Nesya Mutiara Ardana; Nilawati Fiernaningsih; Rachma Bhakti Utami (Politeknik Bisnis Indonesia, 2024)
This research aims to explore and analyze the relationship between shopping motivation using the Shopee application and socio-demographic factors: age, gender, education, occupation, location of residence and shopping capital preferences. With the development of the digital age, the marketing strategy includes an online system for selling its products. Online shopping has become a habit for some people because of the convenience it provides, many people think that online shopping is a means of finding the items they need. This research uses descriptive qualitative methods. Data collection techniques were carried out using interviews and questionnaires. The results of this research show that students and the public shop online due to the influence of advertising and ease of shopping and the influence of friends.